1998
DOI: 10.1287/trsc.32.4.380
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Optimization Models for Train Routing and Scheduling

Abstract: The aim of this paper is to present a survey of recent optimization models for the most commonly studied rail transportation problems. For each group of problems, we propose a classification of models and describe their important characteristics by focusing on model structure and algorithmic aspects. The review mainly concentrates on routing and scheduling problems since they represent the most important portion of the planning activities performed by railways. Routing models surveyed concern the operating pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
282
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 658 publications
(304 citation statements)
references
References 107 publications
(67 reference statements)
0
282
0
10
Order By: Relevance
“…Given its importance, the problem has been widely studied in the literature on railway optimization; for surveys on the specific problem as well as on the use of combinatorial optimization in railway planning see, e.g., [6,7,10,14,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given its importance, the problem has been widely studied in the literature on railway optimization; for surveys on the specific problem as well as on the use of combinatorial optimization in railway planning see, e.g., [6,7,10,14,19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…how many trains are operated relative to the conditions of the network. A survey of optimization models for railway related problems is given by Cordeau et al [5]. This survey describes various optimization models developed for railway problems.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…This belief is supported by the fact that nowadays OR models and techniques play a major role in several railway companies during the planning phase, where the focus is on a good balance of the service level offered to the passengers and efficiency of the resources rolling stock and crew. For an overview on these models and techniques, we refer to surveys of Assad [2], Cordeau et al [5], and Huisman et al [10]. Moreover OR models have proven to be quite effective already for supporting disruption management processes in the airline context, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A state-of-the-art review of literature and practice revealed a lot of research in mathematical models for macroscopic timetable optimization (ON-TIME 2013), see also the review papers by Bussieck et al (1997), Cordeau et al (1998), Caprara et al (2007), and Lusby et al (2011). These macroscopic models rely implicitly on reliable input data which may not always be available.…”
Section: Introductionmentioning
confidence: 99%